POLITENESS STRATEGY USED BY JESS NO LIMIT AND MIAWAUG WHILE PLAYING RIDE OUT HEROES (ROH) TOGETHER (MABAR) - Pradinda, Yulia; Tarigan, Abigail Putri Chrissantha; Sasmita, Rheina; Rangkuti, Rahmadsyah (Ma Chung Press, 2024)
This research aims to analyze the types of politeness strategies used by Jess No Limit and MiawAug during their Ride Out Heroes (ROH) gameplay, using Brown and Levinson’s (1987) theory. The descriptive qualitative method was employed in this study, with data sourced from the transcript of the YouTube gaming video where Jess No Limit and MiawAug played together (mabar) the ROH game. It was uploaded on MiawAug’s YouTube channel on November 1, 2019. The data included utterances from Jess No Limit and MiawAug that contained politeness strategy. Data were collected using documentation and note-taking techniques and analyzed through content analysis. The results indicate that 250 utterances containing politeness strategy were identified, with Jess No Limit contributing 107 and MiawAug contributing 143 utterances. Specifically, Jess No Limit used bald on record 20%, positive politeness 68%, negative politeness 8%, and off-record 4%. MiawAug used bald on record 32%, positive politeness 51%, negative politeness 11%, and off-record 6%. Jess No Limit and MiawAug predominantly used positive politeness strategy, highlighting their focus on maintaining a friendly and cooperative interaction during gameplay.